Association study of gut flora in Wilson's disease through high-throughput sequencing. Issue 31 (August 2018) - Geng, Hao; Shu, Shan; Dong, Jianjian; Li, Hai; Xu, Chenchen; Han, Yongsheng; Hu, Jiyuan; Han, Yongzhu; Yang, Renmin; Cheng, Nan
Abstract : Abstract: In this study, we analyzed the difference of intestinal flora polymorphisms between Wilson's disease (WD) patients and healthy people by high-throughput sequencing technology, and explored the correlation between WD and intestinal flora polymorphism. A total of 22 cases of WD patients and 22 healthy persons as control were recruited. The total DNA was extracted from the fecal specimens of all the subjects, V4 high variable region of 16S rRNA gene was amplified and sequenced by high-throughput sequencing. The sequencing results were analyzed by α diversity and β diversity. The unweighted UniFrac distance matrices were calculated and trees were built by unweighted-pair group method with arithmetic mean (UPGMA). A total of 2, 548, 262 sequences were obtained after the data are optimized, the average sequences in the WD group was 36, 836 ± 4104 and it was 35, 051 ± 3075 in the normal control group, there was no significant difference in the average sequence number between the 2 groups. OTU analysis showed that 2663 OTU were obtained in WD group, and 3271 OTU were obtained in the control group, of which 941 were common OTU. Colony diversity analysis showed that the intestinal flora of WD group and control group belonged to 5 phyla, they were Bacteroidetes, Firmicutes, Proteobacteria, Fusobacteria, and Tenericutes, respectively. In WD group, the abundance of Bacteroidetes was significantly lower than that of the control group (67.19% vs 76.75%, P < .001), and the abundance of Firmicutes (26.18% vs 19.83%, P < .001), Proteobacteria (4.31% vs 3.09%, P < .05), Fusobacteria (1.88% vs 0.04%, P < .001) were significantly higher than that of control group. Compared with the control group at the level of the genus, the abundance of Bacteroides (4.85% vs 4.6%, P < .05), Faecalibacterium (2.92% vs 2.13%, P < .05), Megamonas (0.84% vs 0.22%, P < .001), Lachnospira (0.16% vs 0.09%, P < .001) significantly increased in WD group, while the abundance of Prevotella (1.63% vs 2.48%, P < .001), Roseburia (0.75% vs 1.39%, P < .001) and Phascolarctobacterium (1.72% vs 2.45%, P < .001) significantly decreased in WD group. PCoA and UPGMA tree analysis showed that there were significant differences of gut microbial compositions between the 2 groups. The diversity and composition of intestinal flora in the WD patients were significantly lower than those in the healthy controls, and the diversity of intestinal flora may be associated with the presence of WD.